1997
DOI: 10.1542/peds.99.4.e11
|View full text |Cite
|
Sign up to set email alerts
|

Does Light-to-Moderate Alcohol Consumption During Pregnancy Increase the Risk for Renal Anomalies Among Offspring?

Abstract: ABSTRACT. Objective. To determine the association between light-to-moderate prenatal alcohol exposure and congenital renal anomalies.Methods. Data from the population-based Atlanta Birth Defects Case-Control Study were used to examine the association between selected renal anomalies and self-reported maternal alcohol consumption during the period from 1 month before through 3 months after conception. Case infants were ascertained by a populationbased birth defects registry with active case ascertainment; the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 34 publications
2
26
0
1
Order By: Relevance
“…anomalies, but these results may not be generalizable because all cases had multiple birth defects (Li et al, 1996). Periconceptional maternal use of alcohol was associated with renal agenesis only in a previous study investigating different CAKUT phenotypes (Moore et al, 1997). One other study by Parikh et al (2002) showed a nearly statistically significant association between drinking alcohol and renal agenesis, which was not reproduced by others unless exposure was limited to binge drinking in the second month of pregnancy.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…anomalies, but these results may not be generalizable because all cases had multiple birth defects (Li et al, 1996). Periconceptional maternal use of alcohol was associated with renal agenesis only in a previous study investigating different CAKUT phenotypes (Moore et al, 1997). One other study by Parikh et al (2002) showed a nearly statistically significant association between drinking alcohol and renal agenesis, which was not reproduced by others unless exposure was limited to binge drinking in the second month of pregnancy.…”
Section: Discussionmentioning
confidence: 84%
“…In a few studies, individual phenotypes within the CAKUT spectrum have been investigated and revealed for example increased risks of renal agenesis/hypoplasia for mothers who used alcohol (Moore et al, 1997;Parikh et al, 2002;Slickers et al, 2008). Smoking in early pregnancy was shown to be associated with kidney but not with urinary tract anomalies (K€ all en, 1997;Slickers et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is no consensus in the literature as to what should be considered light drinking. Suggestions are Ͻ9 mL/d (810 mL/trimester) of ethanol (15) or fewer than three standard drinks per week (25), which would be approximately 6.5 mL/d (585 mL/ trimester) of ethanol, considering a content of 14.7 mL (0.5 fluid oz) of absolute ethanol in a standard drink (26). Taking into consideration these data, we set 700 mL/trimester as the highest limit to be considered a light drinker.…”
Section: Methodsmentioning
confidence: 99%
“…No entanto, a exposição é maior para o concepto porque o metabolismo e a eliminação são mais lentos; o líquido amniótico fica impregnado de álcool não-modificado e de acetaldeído, pois não possui a quantidade necessária de enzimas para sua biodegradação 3,4 . Os danos fetais são diferentes, conforme o período gestacional: no primeiro trimestre da gestação, o risco é de anomalias físicas e dismorfismo; no segundo, há risco de abortamento e, no terceiro, pode ocorrer diminuição do crescimento fetal, em especial o perímetro cefálico e o cérebro 5,6 . Em 1988, o Congresso Norte-americano aprovou a lei que obriga a colocação de aviso no rótulo de bebidas alcoólicas com a mensagem "mulheres grávidas não devem consumir álcool".…”
unclassified